Evaluation of Summer Stress Mitigation Strategies through Plasma Cortisol, Oxidative Markers and Conception Rates in Jaffarabadi Buffaloes (Bubalus bubalis) - Borakhatariya, Devasee N; Vala, Karshan B; Vijyeta, Hardeep P; Karangiya, Vijay K; Singh, Vivek K; Patbandha, Tapas (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The current study was executed on postpartum (45-60 days) Jaffarabadi buffaloes from March to June 2023 (summer season), aimed at ascertaining how summer stress mitigation protocols affect conception rates and different biomarkers associated with oxidative stress of summer. The open animals were subjected to timed artificial insemination (TAI) Ovsynch protocol of estrus induction cum synchronization, and responded 24 buffaloes were randomly assigned to four different treatment/mitigation protocols or groups after AI (n=06 per protocol), viz., the NSAID protocol, the antioxidant protocol, the P4 protocol, and a control group. The percent conception rates at 35th day (USG) and at 60th day (per rectal palpation) in buffaloes under four groups were 50.00 and 0.00 %, 50.00 and 33.34%, 16.67 and 16.67%, and 16.67 and 16.67%, respectively, indicating embryonic loss between day 35 and 60 post-AI to the extent of 100% and 33.34% in NSAID and antioxidant treated groups, respectively, and nil in other two groups. The overall mean cortisol concentration was significantly (p<0.05) higher in P4 supplemented than the control group, but it did not vary statistically between conceived, conceived, or animals with embryonic death groups or sampling days. The plasma MDA was significantly (p<0.05) lower in the antioxidant group and higher in the P4 treated group. It also was significantly (p<0.05) higher in animals with embryonic mortality than those of the conceived and non-conceived groups. The TAC level was significantly higher in the antioxidant group and lower in the P4 group. However, among the conceived, non-conceived, and animals with embryonic mortality, as well as across the sampling days, the mean TAC levels did not differ significantly. It was concluded that oxidative stress was the reason behind the embryonic losses in Jaffarabadi buffaloes, and that no treatment protocol was able to improve the summer conception rate.